Ultimatum Game: Sebuah Eksperimen Ekonomi Dalam Kelas - Siswanto, Bambang (Manajemen Bisnis Kompetensi, 2019)
Ultimatum game is one of the game theory models used in an experiment to show the behavior of economic agent decision making that deviates from the basic principles of microeconomic theory. An experimental unit with a game consists of two participants, each called the first player (proposer) and the second player (responder). This study discusses the use of ultimatum games in economic experiments in the classroom. The purpose of this study is to determine the average proposal offered by the first player (proposer) and the average proposal that is not rejected by the second player (responder). The experiment participants were 15 people and each of them participated in the same experiment three times. In each experiment each played the role of first player and second player. Placement of participants in the experimental unit is done randomly. The experimental results show that for the whole experiment the average offer value is 66.16 for the proposer and 33.84 for the responder; while the average value of offers that were not rejected by respondents was 64.50 for proposers and 35.50 for respondents. Most of the behaviors of respondents who refuse offers are consistent with the distributional preferences theory.Keywords: ultimatum game, classroom experiment, fairness, distributional preferences